2017
DOI: 10.1002/polb.24308
|View full text |Cite
|
Sign up to set email alerts
|

Tuning hydrophobicity of a fluorinated terpolymer in differently assembled thin films

Abstract: In the current report, casting from good solvent (acetone) and casting from mixed solvent and nonsolvent were employed for preparing thin films of terpolymer of Tetrafluoroethylene (TFE), Hexafluoropropylene (HFP), and Vinylidene fluoride (VDF) (THV), on silicon wafers. These films revealed various morphologies and wetting behaviors depending on the solution concentration, temperature, and thin film preparation method. The THV thin films prepared by casting from good solvent showed smooth morphology with holes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
(139 reference statements)
1
4
0
Order By: Relevance
“…From XPS, it was determined that THV thin films prepared by casting from a good solvent (the solvent that is able to dissolve the terpolymer) and exhibiting hydrophobicity with water (contact angle around 100°) had very low or essentially zero percentage of -CF 2 and -CF 3 groups at the top most layers of the films. Conversely, the percentage contributions of the same lower surface energy functional groups in the XPS spectra of the THV thin films prepared from mixed solvent and nonsolvent were higher than the corresponding ones prepared by casting from a good solvent (47). Similar to the previous study on THV thin films (31), there was also direct correlation observed between roughness and hydrophobicity of THV thin films by atomic force microscopy (47).…”
Section: Hydrophobicitysupporting
confidence: 81%
See 2 more Smart Citations
“…From XPS, it was determined that THV thin films prepared by casting from a good solvent (the solvent that is able to dissolve the terpolymer) and exhibiting hydrophobicity with water (contact angle around 100°) had very low or essentially zero percentage of -CF 2 and -CF 3 groups at the top most layers of the films. Conversely, the percentage contributions of the same lower surface energy functional groups in the XPS spectra of the THV thin films prepared from mixed solvent and nonsolvent were higher than the corresponding ones prepared by casting from a good solvent (47). Similar to the previous study on THV thin films (31), there was also direct correlation observed between roughness and hydrophobicity of THV thin films by atomic force microscopy (47).…”
Section: Hydrophobicitysupporting
confidence: 81%
“…Conversely, the percentage contributions of the same lower surface energy functional groups in the XPS spectra of the THV thin films prepared from mixed solvent and nonsolvent were higher than the corresponding ones prepared by casting from a good solvent (47). Similar to the previous study on THV thin films (31), there was also direct correlation observed between roughness and hydrophobicity of THV thin films by atomic force microscopy (47). In this study, the indentations increased the roughness, which in turn increased the water contact angle.…”
Section: Hydrophobicitymentioning
confidence: 71%
See 1 more Smart Citation
“…Note that for polymer thin films, it was shown that a mixture of miscible solvent and non-solvent could change the morphology of the polymer thin films. 70 In the second step of wetting with a non-solvent of polymers (e.g. water), a stronger interaction between the non-solvent [71][72] and the alumina surface causes the polymer solution to be isolated in the center of the nanopores, resulting in polymer nanorods 71 or nanospheres.…”
Section: Microwave Annealing Induced Nanowetting (Main)mentioning
confidence: 99%
“…Polystyrene/THV gradient multilayer films could be prepared by forced‐assembly coextrusion . Other studies addressed the behavior of THV at solid interfaces …”
Section: Introductionmentioning
confidence: 99%